Nurturing a Daoist-inspired classroom pedagogy through the contemplative lenses of teacher diaries - Jeffrey, David McLachlan (Current perspectives on Confucianism, Taoism, Buddhism, and education., 2024)
"The harmonizing influence of ancient Daoist philosophy is of much relevance to the world in which we live today, and this is especially so in the field of global education. Among the growing numbers of contemporary teachers and scholars who nurture Daoist wisdom in their classrooms, this book takes the unique pathway of considering its applications through the contemplative lenses of teacher diaries. Its South African born author has taught academic English for over three decades in Japan, the Middle East, and the People's Republic of China. Since early childhood, he has infused his fascination for Daoist wisdom with his enjoyment of writing diaries and in ways that derive insights into the compassionate, frugal, and humble foundations of Daoist-inspired pedagogies within contemporary classroom environments. This book presents Daoist wisdom in terms of it being the Supreme Ultimate of all ways. It introduces the classical Daoist texts of the Laozi, the Zhuangzi, and the Liezi, and shares a short historical overview of Daoism with its growing global influence. As such, it emphasizes that Daoist-inspired pedagogies encourage a delicate balance between intuitive insights and intellectual analysis and in ways that are not antagonistic toward each other, but which dance together as one. In this regard, the role of meditation during the undertaking of diaries is specifically highlighted concerning its propensity to bring one into the present moment, pacify racing thoughts, and transcend the ego. It also shows how a meditative state of mind that accompanies the reading, writing, and analysis of the diary entries contributes to deeper self discernment along with unique intuitive insights related to oneself as a teacher and the classroom environment. In addition, this book describes how the Wordsmith Tools Program and the Book of Changes can be used as additional approaches to analyzing thought patterns within the diary entries and how these also nurture inward contemplations and the intuitive insights that accompany them. Thereafter, considerations based on the applications of core Daoist principles for classroom pedagogies are filtered through the contemplative lenses of teacher diaries. These principles are the unintentional integrity of de, the complementary duality of yin yang, the cosmic vitality of qi, the self so ness of ziran, the unforceful spontaneity of wuwei, and the unblemished purity of pu. This book illustrates through its diary lenses how these six Daoist principles can be nurtured in ways that contribute to a scholarliness that is grounded in an equal appreciation for the logical applications of intelligence along with the uniqueness of intuitive creativity which cannot be explicitly taught but which spontaneously arises from within the deep reservoirs of intuitive wisdom which exist within the true selves of everyone. In addition, this book shares pearls of Daoist wisdom for teachers from within the poetic chapters of the Laozi, as well as within the amusingly enlightening stories in the Zhuangzi and the Liezi such that their ancient teachings can be applied to Daoist inspired pedagogies, and nurtured in ways that unite the joyfulness and scholarly efficacy of both teaching and learning. It is shown how doing so enhances a sense of awe, wonder, openness, and contemplative oneness within the classroom environment making it a happier, more contented, and more meaningful place for both teachers and students"-- Provided by publisher.